Using a Failing Human Ventricular Cardiomyocyte Model to Re-Evaluate Ca2+ Cycling, Voltage Dependence, and Spark Characteristics - Jerome Anthony E. Alvarez; Mohsin Saleet Jafri; Aman Ullah (Biomolecules)
Previous studies have observed alterations in excitation–contraction (EC) coupling during end-stage heart failure that include action potential and calcium (Ca2+) transient prolongation and a reduction of the Ca2+ transient amplitude. Underlying these phenomena are the downregulation of potassium (K+) currents, downregulation of the sarcoplasmic reticulum Ca2+ ATPase (SERCA), increase Ca2+ sensitivity of the ryanodine receptor, and the upregulation of the sodium–calcium (Na=-Ca2+) exchanger. However, in human heart failure (HF), debate continues about the relative contributions of the changes in calcium handling vs. the changes in the membrane currents. To understand the consequences of the above changes, they are incorporated into a computational human ventricular myocyte HF model that can explore the contributions of the spontaneous Ca2+ release from the sarcoplasmic reticulum (SR). The reduction of transient outward K+ current (Ito) is the main membrane current contributor to the decrease in RyR2 open probability and L-type calcium channel (LCC) density which emphasizes its importance to phase 1 of the action potential (AP) shape and duration (APD). During current-clamp conditions, RyR2 hyperphosphorylation exhibits the least amount of Ca2+ release from the SR into the cytosol and SR Ca2+ fractional release during a dynamic slow–rapid–slow (0.5–2.5–0.5 Hz) pacing, but it displays the most abundant and more lasting Ca2+ sparks two-fold longer than a normal cell. On the other hand, under voltage-clamp conditions, HF by decreased SERCA and upregulated INCX show the least SR Ca2+ uptake and EC coupling gain, as compared to HF by hyperphosphorylated RyR2s. Overall, this study demonstrates that the (a) combined effect of SERCA and NCX, and the (b) RyR2 dysfunction, along with the downregulation of the cardiomyocyte’s potassium currents, could substantially contribute to Ca2+ mishandling at the spark level that leads to heart failure.